2012
DOI: 10.1016/j.respol.2012.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship: Exploring the knowledge base

Abstract: Entrepreneurship research has a long tradition and since the 1980s the field has grown significantly. In this study we identify the ‘knowledge producers’ who have shaped the field over time and their core entrepreneurship research works. A unique database consisting of all references in twelve entrepreneurship ‘handbooks’ (or state-of-the-art books) has been developed. The chapters in these handbooks were written by experts within the field, and it can be assumed that the most frequently cited references repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
259
0
25

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(286 citation statements)
references
References 64 publications
2
259
0
25
Order By: Relevance
“…For the majority of the 20th century, interest in entrepreneurs was limited (Landström et al, 2012). Large firms had emerged in the late 19th century with higher levels of productivity and innovation (Chandler, 1990;Henrekson, 2005;Schumpeter, 1942).…”
Section: The Genealogy Of Entrepreneurship Policymentioning
confidence: 99%
See 2 more Smart Citations
“…For the majority of the 20th century, interest in entrepreneurs was limited (Landström et al, 2012). Large firms had emerged in the late 19th century with higher levels of productivity and innovation (Chandler, 1990;Henrekson, 2005;Schumpeter, 1942).…”
Section: The Genealogy Of Entrepreneurship Policymentioning
confidence: 99%
“…The roots of this new entrepreneurship-focused economic model trace back from implementation in the late 1970s, to Chicago in the 1950s, and back to Vienna in the 1930s (Judt, 2010: 13;Mirowski, 2007 Hebert and Link (2006, p393) classified entrepreneurial theories into three groups: the Austrian figure significantly in entrepreneurship citations (Landström et al, 2012). 4 Their worldview was framed by the turmoil of the collapse of the Austro-Hungarian Empire, World War I, the Great Depression, banking crises, stagflation, economic dislocation, labor revolt, the establishment of "Red Vienna," a civil war and then reactionary coup in 1934, and finally a Nazi invasion and World War II.…”
Section: The Austrian Roots Of Entrepreneurship Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…To address such a gap, we propose a bibliometric study that covers the years from 1985 to 2015. In fact, bibliometric studies have shown their usefulness in a broad range of fields such as management (Podsakoff et al, 2008), entrepreneurship (Landström et al, 2012;Marzi et al, 2017a;2017b), expatriates , corporate social responsibilities , supply chain ( Gonzalez-Loureiro, et al, 2015), operations management (Hsieh & Chang, 2009;Zhu et al, 2015), and innovation (Fagerberg et al, 2012;Appio et al, 2016) by helping scholars to sort the streams of research from the "tangled forest" of the scientific proliferation. Thus, the data collected in this paper covers thirty years of research in such a field allowing scholars to have a wider picture of the knowledge base created.…”
Section: Introductionmentioning
confidence: 99%
“…Landström and Benner 2013;Landström, Harirchi, and Åström 2012;Watson 2013;Welter and Lasch 2008). Through classroom vignettes, and a discussion of deities, rituals, and ideas of salvation evident in EE, we discuss how the institutionalisation of entrepreneurship involves a normative promotion of beliefs and values and therefore compares with forms of evangelising (Tedmanson et al 2012;Du Gay 1996).…”
Section: Introductionmentioning
confidence: 99%